Study on overburden failure characteristics and displacement rule under the influence of deep faults - Zhang, Pei-Ding; Wu, Yong-Jiang; Cao, Zheng-Zheng; Li, Zhen-Hua; Du, Feng; Wang, Wen-Qiang; Zhai, Ming-Lei (Frontiers in Earth Science, 2024)
Deep faults significantly impact the structural stabilities and deformation behaviors of their overburden rocks, which are key factors in underground engineering and geological hazard research. Considering the problem of deep-fault-overburdened breaking during mining of super-thick coal seams and taking the Yaoqiao Coal Mine as the research object, the mining fracture evolution characteristics and overburden displacement law of the non-structured and fault-bearing overburden corresponding to fully mechanized caving mining are compared and analyzed using numerical simulations and physical similarity simulations. The results of this study show the following: 1) The fracture height of the overlying rock presents a specific change law with advancement of the working face; the initial rapid increase to a maximum height of 74 m is achieved when the working face advances to 90 m; with the development of the plastic zone indicating past yield, the fracture height decreases to 54 m and becomes stable, and the final caving angle of the fracture stabilizes at 70°. 2) In coal mining under normal fault conditions, when the working face advances from the upper to lower walls, the roof forms a masonry beam structure that slows down fault activation and crack development. When moving away from the fault, the overburden movements and water-conducting cracks are fewer, and the crack height is lower than that without faults. When approaching the fault, the influence of the faults in the fracture zone increases, and the height of fracture development reaches the maximum value after crossing the fault, highlighting the significant influence of the fault on fracture development. 3) Through a similarity simulation test, it is shown that the overburden caving zone is further compacted by the overburden rock and that the roof collapses in a large range, resulting in rapid upward development of the overburden rock cracks and separation of the central overburden rock cracks that are gradually compacted and closed. These findings are expected to have important theoretical and practical significance for deep underground engineering design, geological disaster prevention, and fault activity monitoring.